Polypyrrole / cobalt / nitrogen-doped carbon composite material with coaxial hollow structure and preparation method of polypyrrole / cobalt / nitrogen-doped carbon composite material
The coaxial hollow structure of polypyrrole/cobalt/nitrogen doped carbon composite material is constructed through the template limited-domain growth-MOF topological pyrolysis-in-situ oxidation polymerization strategy, which solves the problems of traditional absorbing materials thickness and narrow bands, and realizes lightweight electromagnetic wave absorption in broadbands, enhancing interface polarization and electromagnetic energy consumption.
Patent Information
- Application Number
- CN202510807627.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-08-19
AI Technical Summary
Traditional absorbent materials have too large thickness, narrow absorption frequency band and too high density, which is difficult to meet the demand of the new generation of aerospace equipment for "wide, light, thin, and strong" absorbent materials, and the interface polarization strength between heterogeneous components and carbon matrix is limited.
The three-stage collaborative preparation strategy of template domain growth-MOF topological pyrolysis-in-situ oxidation polymerization was adopted to construct a coaxial hollow structure of polypyrrole/cobalt/nitrogen doped carbon composite material. The interface chemical bond between cobalt particles and carbon matrix was achieved through ZIF-67 domain growth and polypyrrole coating, forming a nitrogen-doped porous carbon matrix with the inner core as a nitrogen-doped carbon hollow tube, the intermediate layer was inlaid with cobalt nanoparticles, and the outer layer was a conductive polypyrrole coating layer.
The balance between impedance mismatch between materials and free space is achieved, the microwave propagation path is expanded, the interface polarization is enhanced, the microwave absorption is enhanced, and the excellent electromagnetic wave absorption performance is obtained.
Smart Images

Figure CN120504961A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of advanced functional composite materials, and relates to a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material with multi-level heterogeneous interfaces and a controllable construction method thereof, as well as the application of the material in the field of broadband electromagnetic wave absorption and electromagnetic protection. Background Art
[0002] As the intensity of modern electronic warfare increases exponentially, precision spacecraft electronic systems face multiple threats from radar detection, electromagnetic interference, and high-energy microwave weapons. Traditional absorbing materials, limited by inherent flaws such as excessive thickness, narrow absorption bandwidth, and high density, struggle to meet the urgent demand for "broad, light, thin, and strong" absorbing materials for the new generation of aerospace equipment. This technological bottleneck has prompted researchers to turn their attention to micro- and nanostructured composite materials. Through precise component design and multi-dimensional structural control, achieving synergistic enhancement of dielectric and magnetic losses has become a key path to breakthroughs in spacecraft electromagnetic stealth technology.
[0003] Multi-scale heterogeneous interface engineering is considered to be one of the most promising strategies to achieve the above goals. When there is a significant dielectric difference between the components on both sides of the heterogeneous interface, the interfacial polarization effect induced by the alternating electromagnetic field can significantly improve the efficiency of electromagnetic energy dissipation. The current mainstream multi-scale heterogeneous interface construction strategy is carried out along two dimensions: one is to achieve impedance matching optimization through the composite of dielectric-magnetic components, such as introducing transition metal nanoparticles into carbon-based materials; the second is to extend the electromagnetic wave propagation path with the help of special microstructure design, such as constructing core-shell structures, porous frameworks, flower-like structures or one-dimensional oriented arrays. It is particularly noteworthy that one-dimensional structures such as nanotubes, nanowires, and nanorods with high aspect ratios can not only provide axial fast charge transfer channels, but their rich surfaces / interfaces can also produce multiple polarization relaxation mechanisms. Jianwei Wang, et al.
Construction of 1D Heterostructure NiCo@C / ZnO Nanorod with EnhancedMicrowave Absorption, Nano-Micro Letters 13 (2021) 175
Solvothermal assisted synthesis of CoFe2O4 / CNTs nanocompositeand their enhanced microwave absorbing properties, Journal of Alloys and Compounds 867 (2021) 159040
N-doped CNTs / CoNi nanochains-carbon hollow microspheres multi-level multi-scale heterogeneous interface structures and microwave absorption properties, Carbon 228 (2024) 119423
[0004] One-dimensional polypyrrole nanotubes (PPy), with their unique chemical properties and surface tunability, offer a solution for strong coupling between heterogeneous components. Current research has combined PPy with materials such as MnO₂ and MoS₂. The numerous heterojunction polarization interfaces significantly enhance the absorption and attenuation of electromagnetic waves, but challenges remain, such as a lack of loss mechanisms. Addressing these bottlenecks, heterostructures derived from metal-organic frameworks (MOFs) offer unique advantages due to their atomic-level compositional tunability and topologically confined growth.
[0005] In order to solve the above-mentioned problem of "component-structure-performance" synergistic optimization, the present invention proposes a cross-scale interface engineering strategy: using a three-step cascade strategy of template confined growth → MOF topological pyrolysis-in situ oxidative polymerization, MOF-derived magnetic carbon materials are cross-scale composited with polypyrrole nanotubes to construct a polypyrrole / cobalt / nitrogen-doped carbon composite material with a coaxial hollow structure. Its coaxial hollow structure effectively balances the impedance mismatch between the material and free space. The tubular structure expands the propagation path of the incident microwave and provides more transmission paths for electrons. The heterogeneous interface produces rich interface polarization. The magnetic loss induced by the magnetic cobalt nanoparticles and the dielectric loss characteristics of polypyrrole further enhance the consumption of electromagnetic energy. Therefore, the combination of dielectric-magnetic synergistic effect and the rational design of the coaxial hollow tubular structure jointly promotes the enhancement of microwave absorption. Summary of the Invention
[0006] The present invention is directed to the current heterogeneous components (such as ) and the carbon matrix, resulting in limited interfacial polarization and impedance mismatching. This paper provides a coaxial hollow polypyrrole / cobalt / nitrogen-doped carbon composite material, preparation method, and application. This invention innovatively constructs a three-stage synergistic preparation system: template-confined growth, MOF topological pyrolysis, and in situ oxidative polymerization. By controlling the pyrolysis of the precursors, the hierarchical assembly of cross-scale heterostructures is achieved. The constructed polypyrrole / cobalt / nitrogen-doped carbon exhibits a unique coaxial sandwich structure: a core of nitrogen-doped carbon hollow tubes (formed by carbonization of polypyrrole nanotubes), a middle layer of a nitrogen-doped porous carbon matrix embedded with cobalt nanoparticles (converted by pyrolysis of a ZIF-67 metal-organic framework), and an outer layer of conductive polypyrrole. The magnetic loss induced by the internal cobalt particles synergizes with the dielectric loss generated by the polypyrrole. The coaxial hollow structure effectively balances the impedance mismatch between the material and free space. The tubular structure expands the propagation path of the incident microwave and provides more transmission pathways for electrons. The heterojunction generates rich interfacial polarization, which together promotes enhanced microwave absorption. The present invention provides a new method for ultra-wideband lightweight electromagnetic wave absorption of multi-scale dielectric-magnetic composite materials, which is in line with the development direction of absorbing materials.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material comprises the following three-step cascade process:
[0009] In the first step, hollow polypyrrole nanotubes were synthesized by the soft template method.
[0010] Methyl orange was dissolved in deionized water to form a clear orange solution. Anhydrous ferric chloride was added and stirred until completely dissolved. Pyrrole monomer was then added and stirred continuously at room temperature. After the reaction was complete, the solution was filtered, washed with deionized water and ethanol, and dried to obtain hollow polypyrrole nanotubes.
[0011] Furthermore, in the first step, 0.196-0.393 g of methyl orange, 0.972-1.944 g of anhydrous ferric chloride, and 420-840 μL of pyrrole monomer were added to every 120 mL of deionized water; and the stirring time was 12-24 h.
[0012] In the second step, cobalt / nitrogen-doped carbon was synthesized using a template-guided method.
[0013] Step 2.1, dissolving the polypyrrole nanotubes obtained in the first step in an organic solvent, adding sodium dodecylbenzenesulfonate as a surfactant to impart a functional negatively charged surface to the polypyrrole nanotubes, ultrasonically treating the polypyrrole nanotubes, filtering, washing with an organic solvent, and drying to obtain surface-modified polypyrrole nanotubes;
[0014] Furthermore, in step 2.1, the organic solvent includes methanol or ethanol, preferably methanol; the ultrasonication time is 2-4 hours, preferably 3 hours;
[0015] Furthermore, in step 2.1, 0.2-0.4 g of polypyrrole nanotubes and 0.2-0.4 g of sodium dodecylbenzenesulfonate are added to every 40 mL of organic solvent.
[0016] In step 2.2, the surface-modified polypyrrole nanotubes and cobalt nitrate hexahydrate obtained in step 2.1 are dispersed in an organic solvent and subjected to sonication to obtain solution A; 2-methylimidazole is dissolved in an organic solvent to form a transparent solution, which is referred to as solution B; solution B is added to solution A to obtain a mixed solution, the mixed solution is aged at room temperature, centrifuged multiple times with an organic solvent, and then collected and dried to obtain ZIF-67 / polypyrrole nanotubes;
[0017] Furthermore, in step 2.2, the organic solvent includes methanol or ethanol, preferably methanol; the ultrasonication time is 2-4 hours, preferably 3 hours; and the aging time is 12-36 hours;
[0018] Furthermore, in step 2.2, in solution A, 0.15-0.3 g of surface-modified polypyrrole nanotubes and 0.75-1.5 g of cobalt nitrate hexahydrate are added to every 40 mL of organic solvent; in solution B, 1.7-3.75 g of 2-methylimidazole is added to every 40 mL of organic solvent; the volume ratio of solution A to solution B is 1:1.
[0019] In step 2.3, the ZIF-67 / polypyrrole nanotubes obtained in step 2.2 are calcined under a protective atmosphere to produce cobalt / nitrogen-doped carbon. During this calcination process, the polypyrrole nanotubes undergo structural remodeling, with their pyrrole rings undergoing dehydrogenative condensation to form a nitrogen-doped carbon skeleton with sp² hybridization, while retaining a hollow tubular morphology. Through topological pyrolysis, the organic ligands in the ZIF-67 decompose to form a nitrogen-doped carbon matrix, and the Co²⁺ is reduced to metallic Co nanoparticles.
[0020] Furthermore, in step 2.3, the calcination temperature is 700-800° C., the calcination time is 3-4 h, and the protective gas is one of argon and nitrogen.
[0021] The third step is to coat the outer surface of the cobalt / nitrogen-doped carbon with a secondary polypyrrole layer using an in-situ oxidative polymerization method to construct a coaxial hollow heterostructured polypyrrole / cobalt / nitrogen-doped carbon composite. In this step, the interfacial chemical bonding between the cobalt particles and the carbon matrix is enhanced through the confined pyrolysis of ZIF-67 in the second step and the polypyrrole coating in the third step, giving the composite broadband microwave absorption properties. Specifically:
[0022] Step 3.1, dispersing the cobalt / nitrogen-doped carbon prepared in the second step in water, adding the dopant and pyrrole, and mixing them uniformly in an ice-water bath after ultrasonic treatment;
[0023] Furthermore, in step 3.1, 0.1 g to 0.3 g of dopant and 0.1 mL to 0.3 mL of pyrrole are added to every 10 mL of water; the mass volume ratio of the cobalt / nitrogen-doped carbon to pyrrole is (1 g:1 ml) to (1 g:3 ml).
[0024] Furthermore, in step 3.1, the dopant includes dodecylbenzenesulfonic acid and α-naphthalenesulfonic acid.
[0025] In step 3.2, an oxidant is added to carry out oxidative polymerization. After the reaction is completed, the mixture is filtered, washed with water, washed with alcohol, and dried to obtain a polypyrrole / cobalt / nitrogen-doped carbon composite material; the reaction temperature is 0-5°C, and the reaction time is 6-12 h.
[0026] Furthermore, in step 3.2, the oxidant includes ferric chloride hexahydrate and ammonium persulfate, and the amount of the oxidant added is 0.92-2.76 g.
[0027] A coaxial hollow-structured polypyrrole / cobalt / nitrogen-doped carbon composite material is prepared using the above-mentioned preparation method; the polypyrrole / cobalt / nitrogen-doped carbon composite material has a unique coaxial sandwich structure: the inner core is a nitrogen-doped carbon hollow tube (formed by carbonization of polypyrrole nanotubes), the middle layer is a nitrogen-doped porous carbon matrix inlaid with cobalt nanoparticles (converted by pyrolysis of ZIF-67 metal-organic framework), and the outer layer is a conductive polypyrrole coating layer.
[0028] The invention discloses an application of a coaxial hollow structured polypyrrole / cobalt / nitrogen-doped carbon composite material, which can be used as an electromagnetic wave absorbing material.
[0029] The innovation of this invention is that it adopts a three-step cascade strategy of template confined growth → MOF topological pyrolysis → in situ oxidative polymerization to cross-scale composite ZIF-67 and polypyrrole nanotubes, and designs and synthesizes a polypyrrole / cobalt / nitrogen-doped carbon composite with a coaxial hollow structure. The in situ confined growth of ZIF-67 on the polypyrrole surface is achieved through surfactant-induced electrostatic self-assembly; the Co² The reduction migration and in-situ doping of nitrogen elements solve the current heterogeneous components (such as ) and the carbon matrix due to the difficulty in forming strong chemical bonds, which leads to limited interface polarization strength and other key technical difficulties, effectively improving the electromagnetic wave absorption performance.
[0030] The beneficial effects of the present invention are:
[0031] (1) In the three-step cascade strategy of the present invention, the product of the previous step provides the structural basis and active sites for the subsequent steps, successfully achieving the in situ confined growth and stable binding of ZIF-67.
[0032] (2) The present invention has high reproducibility and high yield, and the method is simple and easy to operate.
[0033] (3) By adjusting the proportion of polypyrrole in the composite material, good impedance matching and large dielectric loss can be achieved, thereby obtaining excellent electromagnetic wave absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The microscopic morphology characterization images of Example 1: Figure (a) is a scanning electron microscope image at a 500 nm scale; Figure (b) is a scanning electron microscope image at a 1 μm scale; Figure (c) is a scanning electron microscope image at a 2 μm scale; Figure (d) is a transmission electron microscope image at a 500 nm scale; Figure (e) is a transmission electron microscope image at a 100 nm scale; Figure (f) is a transmission electron microscope image at a 20 nm scale.
[0035] Figure 2This is the EDS element surface scan of Example 1: Figure (a) is the element distribution map; Figure (b) is the carbon element; Figure (c) is the nitrogen element; Figure (d) is the cobalt element.
[0036] Figure 3 This is a scanning electron microscope image of Example 2.
[0037] Figure 4 This is a scanning electron microscope image of Example 3.
[0038] Figure 5 This is the scanning electron microscope image of Comparative Example 1.
[0039] Figure 6 The X-ray diffraction spectra of Examples 1-3 and Comparative Example 1 are shown.
[0040] Figure 7 This is the reflection loss curve of Example 1.
[0041] Figure 8 This is the reflection loss curve of Example 2.
[0042] Figure 9 This is the reflection loss curve of Example 3.
[0043] Figure 10 This is the reflection loss curve of Comparative Example 1. DETAILED DESCRIPTION
[0044] The present invention will be described in detail below with reference to the accompanying drawings and embodiments, but the specific implementation manner of the present invention is not limited thereto.
[0045] Example 1 Preparation method of polypyrrole / cobalt / nitrogen-doped carbon composite material
[0046] Step 1: Dissolve 0.196 g of methyl orange in 120 mL of deionized water to form a clear orange solution. Add 0.972 g of anhydrous ferric chloride and stir until completely dissolved. Then, inject 420 μL of pyrrole monomer and continue stirring at room temperature for 12 hours. After the reaction is complete, filter, wash with deionized water and ethanol, and dry to obtain hollow polypyrrole nanotubes.
[0047] Step 2: Dissolve 0.2 g of the above-mentioned polypyrrole nanotubes in 40 mL of methanol, add 0.2 g of sodium dodecylbenzenesulfonate as a surfactant, sonicate for 3 hours, filter, wash with methanol, and dry. Then, take 0.15 g of the above-mentioned powder and 0.75 g of cobalt nitrate hexahydrate and disperse them in 40 mL of methanol. After sonication for 3 hours, obtain solution A. Separately, dissolve 1.7 g of 2-methylimidazole in 40 mL of methanol to form a transparent solution as solution B. Solution B is added to solution A to obtain a mixed solution. The mixed solution is aged at room temperature for 24 hours, centrifuged several times with an organic solvent, and then collected and dried to obtain ZIF-67 / polypyrrole nanotubes. The ZIF-67 / polypyrrole nanotubes are placed in a tube furnace and calcined at 700 ° C for 3 hours under argon protection to obtain cobalt / nitrogen-doped carbon;
[0048] Step 3: Disperse 0.1 g of cobalt / nitrogen-doped carbon in 10 mL of water, add 0.1 g of sodium dodecylbenzenesulfonate and 0.1 mL of pyrrole monomer, and mix evenly in an ice-water bath at 0°C after ultrasonic treatment for 30 min; add an aqueous solution containing 0.92 g of ferric chloride hexahydrate (0.6 M) for oxidative polymerization. After reacting for 6 h, filter, wash with water, wash with alcohol, and dry to obtain a polypyrrole / cobalt / nitrogen-doped carbon composite material.
[0049] like Figure 1 As shown, the sample exhibits a rough and clearly distinguishable hollow tubular structure. The lattice spacing in the high-resolution TEM image is 0.204 nm, which can be attributed to the Co (111) plane. In addition, Figure 2 The EDS mapping image shows the uniform distribution of Co, N, C, and O. 0.014 g of the material obtained in step 3 was weighed and mixed with paraffin wax with a filling rate of 10 wt% to form a cylindrical ring with a thickness of about 3.0 mm. Figure 7 The results show that the minimum reflection loss of the sample at a thickness of 3.0 mm is -63.98 dB, and the effective absorption bandwidth is 7.14 GHz (10.86 ~ 18 GHz, 2.0 mm).
[0050] Example 2 Preparation method of polypyrrole / cobalt / nitrogen-doped carbon composite material
[0051] Step 1: Dissolve 0.393 g of methyl orange in 120 mL of deionized water to form a clear orange solution. Add 1.944 g of anhydrous ferric chloride and stir until completely dissolved. Then, inject 840 μL of pyrrole monomer and continue stirring at room temperature for 24 hours. After the reaction is complete, filter, wash with deionized water and ethanol, and dry to obtain hollow polypyrrole nanotubes.
[0052] Step 2: Dissolve 0.4 g of the above-mentioned polypyrrole nanotubes in 40 mL of ethanol, add 0.4 g of sodium dodecylbenzenesulfonate as a surfactant, sonicate for 2 h, filter, wash with ethanol, and dry. Then take 0.3 g of the above-mentioned powder and 1.5 g of cobalt nitrate hexahydrate and disperse them in 40 mL of ethanol, sonicate for 2 h to obtain solution A. Separately, dissolve 3.75 g of 2-methylimidazole in 40 mL of ethanol to form a transparent solution as solution B. Solution B is added to solution A to obtain a mixed solution, and the mixed solution is aged at room temperature for 12 h, centrifuged three times with ethanol, and then collected and dried to obtain ZIF-67 / polypyrrole nanotubes. The ZIF-67 / polypyrrole nanotubes are placed in a tube furnace and calcined at 800 ° C for 4 h under nitrogen protection to obtain cobalt / nitrogen-doped carbon;
[0053] Step 3: Disperse 0.1 g of cobalt / nitrogen-doped carbon in 10 mL of water, add 0.3 g of α-naphthalenesulfonic acid and 0.3 mL of pyrrole monomer, and mix evenly in an ice-water bath at 5°C after ultrasonic treatment for 30 min; add an aqueous solution (0.6 M) containing 2.76 g of ammonium persulfate for oxidative polymerization. After reacting for 12 h, filter, wash with water, wash with alcohol, and dry to obtain a polypyrrole / cobalt / nitrogen-doped carbon composite material.
[0054] The microscopic morphology of the product is Figure 3 As shown, the nanotube-like structure exhibits a rough surface. Weigh 0.014 g of the material obtained in Step 3 and mix it with paraffin wax at a filling ratio of 10 wt%. The result is a cylindrical ring approximately 3.0 mm thick. The minimum reflection loss at a thickness of 3.1 mm is -45.21 dB, and the effective absorption bandwidth is 5.53 GHz (12.47 to 18 GHz, 2.1 mm).
[0055] Example 3 Preparation method of polypyrrole / cobalt / nitrogen-doped carbon composite material
[0056] Step 1: Dissolve 0.295 g of methyl orange in 120 mL of deionized water to form a clear orange solution. Add 1.458 g of anhydrous ferric chloride and stir until completely dissolved. Then, inject 630 μL of pyrrole monomer and continue stirring at room temperature for 18 hours. After the reaction is complete, filter, wash with deionized water and ethanol, and dry to obtain hollow polypyrrole nanotubes.
[0057] Step 2: Dissolve 0.4 g of the above-mentioned polypyrrole nanotubes in 40 mL of methanol, add 0.4 g of sodium dodecylbenzenesulfonate as a surfactant, sonicate for 4 hours, filter, wash with ethanol, and dry. Then take 0.3 g of the above-mentioned powder and 1.5 g of cobalt nitrate hexahydrate and disperse them in 40 mL of methanol. After sonication for 4 hours, obtain solution A. Separately, dissolve 3.75 g of 2-methylimidazole in 40 mL of methanol to form a transparent solution as solution B. Solution B is added to solution A to obtain a mixed solution. The mixed solution is aged at room temperature for 36 hours, centrifuged three times with methanol, and then collected and dried to obtain ZIF-67 / polypyrrole nanotubes. The ZIF-67 / polypyrrole nanotubes are placed in a tube furnace and calcined at 750 ° C for 3.5 hours under nitrogen protection to obtain cobalt / nitrogen-doped carbon;
[0058] Step 3: Disperse 0.1 g of cobalt / nitrogen-doped carbon in 10 mL of water, add 0.2 g of sodium dodecylbenzenesulfonate and 0.2 mL of pyrrole monomer, and mix evenly in a 5°C ice-water bath after ultrasonic treatment for 30 min; add an aqueous solution containing 2.3 g of ferric chloride hexahydrate (0.6 M) for oxidative polymerization. After reacting for 9 h, filter, wash with water, wash with alcohol, and dry to obtain a polypyrrole / cobalt / nitrogen-doped carbon composite material.
[0059] The microscopic morphology of the product is Figure 4 As shown, the nanotube structure with rough surface is presented. Weigh 0.014g of the material obtained in step 3 and mix it with paraffin wax with a filling rate of 10 wt% to make a cylindrical ring with a thickness of about 3.0 mm. Figure 9 As shown in the figure, the minimum reflection loss of the sample at a thickness of 1.5 mm is -48.97 dB, and the effective absorption bandwidth is 4.93 GHz (1.5 mm).
[0060] Comparative Example 1 Preparation method of cobalt / nitrogen-doped carbon composite material
[0061] Step 1: Dissolve 0.196 g of methyl orange in 120 mL of deionized water to form a clear orange solution. Add 0.972 g of anhydrous ferric chloride and stir until completely dissolved. Then, inject 420 μL of pyrrole monomer and continue stirring at room temperature for 12 hours. After the reaction is complete, filter, wash with deionized water and ethanol, and dry to obtain hollow polypyrrole nanotubes.
[0062] Step 2: Dissolve 0.2 g of the aforementioned polypyrrole nanotubes in 40 mL of methanol, add 0.2 g of sodium dodecylbenzenesulfonate as a surfactant, and sonicate for 3 hours. Filter, wash with methanol, and dry. Next, disperse 0.15 g of the aforementioned powder and 0.75 g of cobalt nitrate hexahydrate in 40 mL of methanol and sonicate for 3 hours to obtain Solution A. Separately, dissolve 1.7 g of 2-methylimidazole in 40 mL of methanol to form a transparent solution, designated Solution B. Solution B was added to Solution A to obtain a mixed solution. The mixed solution was aged at room temperature for 24 hours, centrifuged multiple times with an organic solvent, and then collected and dried to obtain ZIF-67 / polypyrrole nanotubes. The ZIF-67 / polypyrrole nanotubes were placed in a tube furnace and calcined at 700°C for 3 hours under argon to obtain a cobalt / nitrogen-doped carbon composite.
[0063] like Figure 5 As shown, the product presents a corncob-like nanotube morphology with uniform protrusions on the surface. Weigh 0.014 g of the material obtained in step 2 and mix it with paraffin wax with a filling rate of 10 wt% to form a cylindrical ring with a thickness of about 3.0 mm. Figure 10 As shown in the figure, the minimum reflection loss of the sample at a thickness of 1.5 mm is -17.27 dB, and the effective absorption bandwidth is 6.46 GHz (3.1 mm). Compared with Example 1, the absorbing composite material of the present invention effectively improves the absorption strength and broadens the absorption bandwidth, showing broad application prospects, particularly in the fields of radar stealth, electronic countermeasures, communication jamming, and military protection.
[0064] The above-described embodiments merely express the implementation methods of the present invention, but should not be understood as limiting the scope of the present invention. It should be pointed out that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, which all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material, characterized in that: The preparation method comprises the following steps: In the first step, hollow polypyrrole nanotubes were synthesized using a soft template method; In the second step, based on the polypyrrole nanotubes synthesized in the first step, cobalt / nitrogen-doped carbon was synthesized using a template-guided method; In the third step, a polypyrrole layer is secondary coated on the outer surface of the cobalt / nitrogen-doped carbon by in-situ oxidative polymerization to construct a coaxial hollow heterostructured polypyrrole / cobalt / nitrogen-doped carbon composite material; specifically: Step 3.1, dispersing the cobalt / nitrogen-doped carbon obtained in the second step in water, adding the dopant and pyrrole, and mixing them uniformly in an ice-water bath after ultrasonic treatment; In step 3.2, an oxidant is added to carry out oxidative polymerization. After the reaction is completed, the mixture is filtered, washed with water, washed with alcohol, and dried to obtain a polypyrrole / cobalt / nitrogen-doped carbon composite material; the reaction temperature is 0-5°C, and the reaction time is 6-12 h.
2. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 1, characterized in that: The first step is specifically as follows: dissolving methyl orange in deionized water to form a clear orange solution, adding anhydrous ferric chloride and stirring until completely dissolved, then injecting pyrrole monomer and continuously stirring at room temperature; After the reaction is completed, post-processing is performed to obtain hollow polypyrrole nanotubes.
3. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 2, characterized in that: In the first step, 0.196-0.393 g of methyl orange, 0.972-1.944 g of anhydrous ferric chloride, and 420-840 μL of pyrrole monomer were added to every 120 mL of deionized water; the stirring time was 12-24 h.
4. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 1, characterized in that: The second step is specifically as follows: Step 2.1, dissolving the polypyrrole nanotubes obtained in the first step in an organic solvent, adding sodium dodecylbenzenesulfonate as a surfactant, and ultrasonically treating for 2-4 hours followed by post-treatment to obtain surface-modified polypyrrole nanotubes; Step 2.2: Dispersing the surface-modified polypyrrole nanotubes and cobalt nitrate hexahydrate obtained in step 2.1 in an organic solvent and sonicating for 2-4 hours to obtain solution A; dissolving 2-methylimidazole in an organic solvent to form a transparent solution, which serves as solution B; adding solution B to solution A to obtain a mixed solution, and aging the mixed solution at room temperature for 12-36 hours to obtain ZIF-67 / polypyrrole nanotubes; Step 2.3, the ZIF-67 / polypyrrole nanotubes obtained in step 2.2 are calcined under gas protection to obtain cobalt / nitrogen-doped carbon.
5. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 4, characterized in that: In the second step: In step 2.1, 0.2-0.4 g of polypyrrole nanotubes and 0.2-0.4 g of sodium dodecylbenzenesulfonate were added to every 40 mL of organic solvent; In step 2.2, in solution A, 0.15-0.3 g of surface-modified polypyrrole nanotubes and 0.75-1.5 g of cobalt nitrate hexahydrate are added to every 40 mL of organic solvent; in solution B, 1.7-3.75 g of 2-methylimidazole is added to every 40 mL of organic solvent; the volume ratio of solution A to solution B is 1:1; In the step 2.3, the calcination temperature is 700-800° C., the calcination time is 3-4 h, and the protective gas is one of argon and nitrogen.
6. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 4, characterized in that: The organic solvent in step 2.1 includes methanol and ethanol; the organic solvent in step 2.2 includes methanol and ethanol.
7. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 1, characterized in that: In the third step, 0.1 g to 0.3 g of dopant, 0.1 mL to 0.3 mL of pyrrole, and 0.92 to 2.76 g of oxidant are added to every 10 mL of water; the mass volume ratio of the cobalt / nitrogen-doped carbon to pyrrole is (1 g:1 mL) to (1 g:3 mL).
8. The method for preparing a coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 1, characterized in that: In step 3.1, the dopant includes dodecylbenzenesulfonic acid and α-naphthalenesulfonic acid; in step 3.2, the oxidant includes ferric chloride hexahydrate and ammonium persulfate.
9. A coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8; the polypyrrole / cobalt / nitrogen-doped carbon composite material has a coaxial sandwich structure: the inner core is a nitrogen-doped carbon hollow tube formed by carbonization of polypyrrole nanotubes, the middle layer is a nitrogen-doped porous carbon matrix inlaid with cobalt nanoparticles, and the outer layer is a conductive polypyrrole coating layer.
10. Use of the coaxial hollow structure polypyrrole / cobalt / nitrogen-doped carbon composite material according to claim 9, characterized in that: The polypyrrole / cobalt / nitrogen-doped carbon composite material can be used as an electromagnetic wave absorbing material.
Citation Information
Cited By
High-strength modified aramid nanofiber as well as preparation method and application thereof
CN120867095A
High-strength modified aramid nanofiber, and preparation method and application thereof
CN120867095B
Modified aramid nanofiber as well as preparation method and application thereof
CN120867096A
Modified aramid nanofiber and preparation method and application thereof
CN120867096B